Komunikasi Interpersonal di Dunia Virtual Remaja Pecandu Mobile Legends di Kelurahan Bojo Baru - Nur Ilham (Interaction: Jurnal Sosiologi Komunikasi, 2025)
Indonesia ranks first in Asia with 6.05 hours of mobile phone use per day, creating a paradox of high virtual connectivity but social isolation in the real world. This study analyses the transformation of interpersonal communication among Mobile Legends-addicted adolescents in Bojo Baru Village using the perspectives of Computer-Mediated Communication and Goffman's dramaturgy. A qualitative case study method was applied to seven informants (five adolescents aged 13-17 who played 8-15 hours/day, two supporting informants) through 200 hours of observation, in-depth interviews, and digital conversation analysis. Five phenomena were identified: (1) "pseudo-intimate relationships" in the form of deep emotional bonds without physical interaction, challenging Granovetter's weak ties theory; (2) performative identities where adolescents become "assertive leaders in the game, quiet at home"; (3) vernacular language with gaming terms that transform into metaphors for life; (4) compensatory mechanisms where games become an escape for introverted adolescents, which actually exacerbates family isolation; (5) "digital jet lag" in the form of temporal disorientation that triggers family conflict and academic decline. The findings show adolescents as active agents constructing a hybrid social reality, where virtual relationships form a parallel system with a different logic from physical interactions. The study contributes to the concept of "digitally mediated strong ties" and recommends holistic interventions that recognise the adaptive function of gaming while addressing its negative impacts through digital literacy and intergenerational dialogue.